Artificial intelligence in medical education: Latin American context - Aguilar Bucheli, Daniel; Borja Espinoza, Marlo Alexander; Cadena Vargas, Emilia Fabiana; Endara Regalado, Stefano Adrián; Endara Sánchez, Daniela Bernarda; Feijóo Jiménez, Danna Leonela; Jácome Castillo, Doménica Alejandra; Jiménez Álvarez, Danna Micaela; Pazmiño Troncoso, Ariel Sebastián; Valladares Izurieta, David Sebastián; Alcocer Veintimilla, Sandra Malena; Herrera Flores, María Belén; et al. (Metro Ciencia, 2023)
Introduction: Artificial Intelligence (AI) is an algorithm and statistic technology used in many human competences. In health, it works as a support tool centered in managing the use of data for clinical performance and learning medical skills, improving the health response from professionals. Methods: This paper collects and analyzes previous research, in electronic databases, related to the use of artificial intelligence in medical education within the Latin American context. No exclusion criteria were applied. Results: Artificial intelligence (AI) is considered an effective support tool for the development of multidisciplinary learning and teaching strategies focused on improving medical care through updating the process in medical training. For its correct use, it is important to define a support approach and its competent training to facilitate its effective implementation, reducing the gap between ethical and legal debates. The Latin American region, due to its political and sociocultural context, presents different challenges that must be faced to integrate these technologies into health education, occupation, and acceptation. Conclusion: In medical education AI is used as a tool which is a support for students and doctors, but it won't be a replacement. In Latin American it is the key for improving the education. AI must be operated or regulated by humans because it doesn't consider civil liberties and it hasn't conscience.